Shirley Chisholm - Aggs, Patrice; Jenai, Markia (Chicago, Illinois : Sunbird Books, 2022)
In graphic novel format looks at the life of American politician, educator, and author, Shirley Chisholm.
3.4
3-6
GN650L
Keywords: Chisholm, Shirley, -- 1924-2005 -- Comic books, strips, etc; Chisholm, Shirley, -- 1924-2005 -- Juvenile literature; African American legislators -- Biography -- Comic books, strips, etc; African American legislators -- Biography -- Juvenile literature; Women legislators -- United States -- Biography -- Comic books, strips, etc; Women legislators -- United States -- Biography -- Juvenile literature; Legislators -- United States -- Biography -- Comic books, strips, etc; Legislators -- United States -- Biography -- Juvenile literature; United States. -- Congress. -- House -- Biography -- Comic books, strips, etc; United States. -- Congress. -- House -- Biography -- Juvenile literature; Teachers -- United States -- Biography -- Comic books, strips, etc; Teachers -- United States -- Biography -- Juvenile literature; Presidential candidates -- United States -- Biography -- Comic books, strips, etc; Presidential candidates -- United States -- Biography -- Juvenile literature; Legislators -- Cartoons and comics; Women -- Biography -- Cartoons and comics; Biographies; Nonfiction comics; Comics (Graphic works); Biographical comics; Graphic novels